Muatan Hikmah At-Tasyri’ dalam Pengembangan Kurikulum Pendidikan Agama Islam - Lutfi, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Islamic religious education today runs conventionally and traditionally. Teachers or educators only teach knowledge or theory to students, without actually appreciating the theory. This failure boils down to the reality that Islamic religious education only focuses on the knowledge (cognitive) aspect in the form of the growth of religious values and ignores other critical aspects. The conative and affective aspects of religious education are sometimes under-noticed. So that the piety of worship sometimes has less impact on the 'anal piety and social piety. The aim of this research is to formulate the development of the Islamic Religious Education curriculum with the content of Hikmah at-Tasyri'. This study employs a qualitative approach with a literature review as its research type. The research objects include primary and secondary literary sources. The findings of this research indicate that the content of Hikmah at-Tasyri' would be highly effective when implemented in the development of the Islamic Religious Education curriculum to shape students with strong character, instilling Islamic values, and enabling them to apply these principles in their daily lives.